In-vitro characterisation of a novel antimicrobial agent, TNP-2092, against Helicobacter pylori clinical isolates (Swiss Medical Weekly, 2018)
BACKGROUND AND OBJECTIVES TNP-2092 is a novel dual-action lead compound consisting of rifamycin SV and 4H-4-oxo-quinolizine pharmacophores, with a broad spectrum of antibacterial activities. This compound is currently in the early stage of clinical development for Helicobacter pylori infection. The aim of the present study was to determine the antibacterial activity of TNP-2092 against H. pylori isolated from primary patients. METHODS A total of 100 H. pylori clinical isolates from primary patients were selected. The minimum inhibitory concentrations (MICs) for clarithromycin, levofloxacin, rifampin and TNP-2092 were determined using an agar dilution method. A time-kill study was performed with different concentrations of TNP-2092 relevant to MIC against H. pylori ATCC strain 43504 for up to 24 hours. The time-kill study with drug concentrations of 0–4 × MIC was also used to determine the antibacterial activity of TNP-2092 against H. pylori under different pH conditions (pH 4–7). RESULTS The primary resistance percentages to clarithromycin, levofloxacin, rifampin and TNP-2092 were 13, 18, 1 and 1%, respectively. TNP-2092 killing kinetics were both concentration and time dependent. The effectiveness of TNP-2092 against H. pylori was gradually reduced with a decrease in pH. CONCLUSIONS TNP-2092 is highly active against H. pylori and against strains resistant to clarithromycin or levofloxacin. Its antibacterial activity is both concentration- and time-dependent .The antibacterial activity of TNP-2092 appears to be pH-dependent and is more active under neutral pH. TNP-2092 represents a promising new therapy for the treatment of H. pylori infection in primary patients.